Factors influencing women’s entrepreneurial intentions: a case study - Raudeliūnienė, Jurgita; Matar, Ibrahim (Journal of Business Economics and Management, 2023)
Studying women’s entrepreneurial intentions is critical not only for encouraging women’s entrepreneurship but also for developing their entrepreneurial competencies. However, in the case of Lebanon, there is still a gap in the scientific studies related to identifying factors influencing women’s entrepreneurial intentions. In order to fulfill this gap, this research analyzes the main factors influencing Lebanese women’s entrepreneurial intentions: dominance, innovativeness, independence, and social encouragement. A scientific literature review was conducted to develop the research model and propose the research hypotheses. A survey questionnaire was prepared and distributed online to collect data from 620 Lebanese women. Then, the collected data was analyzed and presented employing descriptive statistics, inferential statistics, PLS structural equation modeling techniques, and importance-performance map analysis. The findings revealed significant relationships between the research variables except for women’s independence. Also, the findings showed that social encouragement for women partially mediates the relationship between innovativeness and women’s entrepreneurial intentions.